The development and implementation of mobile help desk system- usability acceptance and design issues based on Shackel’s model / Siti Raihana Md Noor - Md Noor, Siti Raihana (Faculty of Information Technology and Quantitative Sciences, 2006)
In the traditional help desk, one person is responsible in handling calls and sorting problem by resorting to various information and knowledge sources. This process is inefficient because many calls are abandoned due to the phone line being busy. Oftentimes, the person who handles the help desk spent time resolving repeat problems. With the advent of Web technology that can provide dynamic, interactive, hypermedia and platform independent, such traditional method become obsolete. In addition, the widespread of mobile technology such as Short Message Service (SMS) has emerged the need to integrate SMS with internet application for both business and leisure. Therefore, Mobile Help Desk System is introduced to explore the technology and thus eliminates problems with traditional help desk. Usability is an important element to consider before we accept any new system. Therefore a usability testing is performed to evaluate the usability of the mobile help desk system based on Shackel’s model that focus on four usability factors; effectiveness, learnability, flexibility and attitude. From the findings, the results of this study indicated that most of students agreed that the mobile help desk system is effective, learnable and flexible. They also felt satisfied after using the system. From the study, we also found that students acceptance toward the mobile help desk system is most highly in positive level. The gender and online help desk experience do not influence their acceptance. This is because most of them are exposed to the information and communication technology. Overall, the development and implementation of mobile help desk system benefit students and contribute some significance to the faculty and university.